PERLINDUNGAN HUKUM TERHADAP DIREKSI DAN DEWAN KOMISARIS PERSEROAN ATAS PEMBERHENTIAN TANPA PEMBERITAHUAN DALAM RAPAT UMUM PEMEGANG SAHAM - Elida Marbun; Nur Hakim; Wira Franciska (SINERGI : Jurnal Riset Ilmiah, 2025)
Article 119 of the Company Law states that the provisions regarding the dismissal of members of the Board of Directors as referred to in Article 105 apply mutatis mutandis to the dismissal of members of the Board of Commissioners. Members of the Board of Directors and Board of Commissioners can be dismissed at any time through the GMS by stating the reasons for their dismissal clearly, but there is no more specific regulation regarding notification obligations or procedures that must be followed, so this causes members of the Board of Directors and Board of Commissioners to be unable to defend themselves. The formulation in this research is what are the legal consequences of dismissal without notification of the Company's Directors and Board of Commissioners at the General Meeting of Shareholders? And what is the legal protection for the Company's Directors and Board of Commissioners for dismissal without notification at the General Meeting of Shareholders? The theories used in this research are the Legal Protection theory according to Satijipto Rahardjo and the Legal Consequences Theory according to R. Soeroso.The method used in this research is normative juridical research in the form of library legal materials or secondary data with primary, secondary and tertiary sources of legal materials. The research approach used is statutory, conceptual, analytical and case approaches as well as techniques for collecting legal materials by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The analysis technique for legal materials is carried out using systematic, grammatical legal interpretation.The research results show that the legal consequences of dismissal the Company's Directors and Board of Commissioners without notification at the GMS are that it is invalid if members of the Board of Directors and Board of Commissioners object to their dismissal. This is because the Board of Directors and Board of Commissioners have the right to know the reasons for dismissal and the right to defend themselves at the GMS as regulated in Article 105 paragraphs (2) and (3) of the Company Law. Thus, all matters relating to the consequences of dismissal which are contrary to applicable regulations are deemed to have never existed. Legal protection for the Company's Directors and Board of Commissioners for dismissal without notification at the GMS is in the form of repressive legal protection, in this case the Directors and Board of Commissioners have the right to file a lawsuit at the District Court in accordance with the location of the Limited Liability Company in question and can make legal appeals to High Court and Supreme Court. The lawsuit filed contains unlawful acts as stipulated in Article 1365 of the Civil Code because the GMS was held contrary to the provisions of the Company Law. Thus, the Board of Directors and Board of Commissioners have the right to obtain compensation for unlawful actions committed by shareholders